Treatment of hypertension in patients with pre-eclampsia: a prospective parallel-group study comparing dihydralazine with urapidil. - Wacker, Jürgen; Werner, Petra; Walter-Sack, Ingeborg; Bastert, Gunther (Nephrology, dialysis, transplantation, 1998)
BACKGROUND: The primary objective of treatment in women with severe hypertension and pre-eclampsia is to prevent complications such as encephalopathy and haemorrhage. In many countries dihydralazine is considered the drug of choice for treating hypertension in pregnancy, because it now has been used safely for about 30 years, and the introduction of a new drug in pregnancy is a difficult task with partially unknown hazards. In some other countries combined alpha- and beta-blockers are also used. Taking into account that some patients with pre-eclampsia do not respond to dihydralazine and the drug has serious side-effects like headache and reflex tachycardia, there is some need for developing alternative treatment strategies using drugs that are more adequate for pregnancy than dihydralazine. METHODS: Urapidil is a post-synaptic alpha 1 adrenoceptor antagonist, which is widely used to control hypertensive crises unrelated to pregnancy. Since it is known that pre-eclampsia is associated with increased sympathetic activity, administration of an alpha 1 adrenoceptor antagonist provides a reasonable therapeutic basis. So far there is only one report describing the i.v. use of urapidil in the treatment of hypertension in pregnancy unresponsive to dihydralazine and one report which describes the oral use of urapidil. In an earlier pilot study we examined the dose range for i.v. application of urapidil necessary for adequate blood pressure control in patients with pre-eclampsia. In the present randomized controlled study 26 white women with pre-eclampsia and hypertension in pregnancy were included. Treatment was not blinded. During the initial period of intensive intravenous treatment all subjects were under constant surveillance by a physician and a nurse. RESULTS: Effective prolonged control of blood pressure (values below 150/100 mmHg) was achieved in all patients of the two groups. In one patient of the dihydralazine group signs of lightheadedness and near syncope were noted. After this side-effect of dihydralazine the patient was treated with urapidil. At the end of the observation period the maternal heart rate in the dihydralazine group was higher than in the urapidil group. CONCLUSIONS: Since urapidil decreased the high blood pressure in patients with pre-eclampsia without serious side-effects urapidil appears preferable superior to dihydralazine. The haemodynamic effects of urapidil were more predictable than those of dihydralazine. The reduction of intracerebral pressure could be an additional advantage of urapidil in the treatment of patients with pre-eclampsia.
Gesehen am 18.03.2024